The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/emm.2017.41
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation and biological function of transmembrane protein 119 in osteosarcoma

Abstract: Osteosarcoma is suggested to be caused by genetic and molecular alterations that disrupt osteoblast differentiation. Recent studies have reported that transmembrane protein 119 (TMEM119) contributes to osteoblast differentiation and bone development. However, the level of TMEM119 expression and its roles in osteosarcoma have not yet been elucidated. In the present study, TMEM119 mRNA and protein expression was found to be up-regulated in osteosarcoma compared with normal bone cyst tissues. The level of TMEM119… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“… 33 However, evidence on the function of TMEM119 in tumorigenesis, especially cell migration and invasion, was extremely limited. Only Jiang et al 19 showed that TMEM119 silencing contributed to decreased migration and invasion of osteosarcoma cells and expression of metastasis-related proteins (MMP2, N-cadherin, E-cadherin, Vimentin, and Twist1), which in part agree with our findings that TMEM119 enhanced invasion and migration of gastric cancer cells as well as the MMP2 and MMP9 expression.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“… 33 However, evidence on the function of TMEM119 in tumorigenesis, especially cell migration and invasion, was extremely limited. Only Jiang et al 19 showed that TMEM119 silencing contributed to decreased migration and invasion of osteosarcoma cells and expression of metastasis-related proteins (MMP2, N-cadherin, E-cadherin, Vimentin, and Twist1), which in part agree with our findings that TMEM119 enhanced invasion and migration of gastric cancer cells as well as the MMP2 and MMP9 expression.…”
Section: Discussionsupporting
confidence: 92%
“…In line with our findings, some studies showed that TMEM119 was overexpressed in osteosarcoma, benign phyllodes tumors of the breast, and prostate cancer. 16 , 17 , 19 However, downregulated TMEM119 expression was observed in oral squamous cell carcinoma. 18 These results suggest that the expression pattern is different in different cancers.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies have demonstrated that osteosarcoma may be involved in genetic and molecular alterations which affect osteoblast differentiation. 14,15 SDF-1/CXCR4 axis was found to play important roles in almost all malignancies including osteosarcoma. 16,17 miRNAs play critical roles in regulating cell processes and may function as oncogenes or tumor suppressors to regulate gene and protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…Both P2RY12 and TMEM119 are expressed by the vast majority of microglia within the healthy CNS. The function of TMEM119 in microglia has not been yet elucidated, but in other cell types, it has been implicated with differentiation and proliferation [39][40][41][42]. P2RY12 serves as a chemotactic receptor that guides microglia to sites of injury [26].…”
Section: Microgliamentioning
confidence: 99%